Curcuma longa L. Extract and Photodynamic Therapy are Effective against Candida spp. and Do Not Show Toxicity In Vivo - Marques Meccatti, Vanessa [UNESP]; De Souza Moura, Larissa [UNESP]; Guerra Pinto, Juliana; Ferreira-Strixino, Juliana; Abu Hasna, Amjad [UNESP]; Alves Figueiredo-Godoi, Lívia Mara [UNESP]; Campos Junqueira, Juliana [UNESP]; Marcucci, Maria Cristina [UNESP]; Paula Ramos, Lucas De [UNESP]; Carvalho, Claudio Antonio Talge [UNESP]; Pucci, Cesar Rogério [UNESP]; De Oliveira, Luciane Dias [UNESP] (Wiley, 2022)
Radiotherapy induces a higher level of Candida spp. colonization, resulting in oral candidiasis. This study aimed to evaluate the phototransformation potential of the glycolic extract of Curcuma longa (C. longa); the antifungal activity of C. longa, curcumin, and antifungal photodynamic therapy (aPDT) with blue light-emitting diodes LEDon Candida albicans and Candida tropicalis in vitro; and the toxicity of C. longa and curcumin in Galleria mellonella model. In order to confirm the light absorption capacity of the C. longa extract, its phototransformation potential was evaluated. The antifungal effect of C. longa, curcumin, and aPDT was evaluated over Candida spp. Finally, the toxicity of C. longa and curcumin was evaluated on the Galleria mellonella model. The data were analyzed using the GraphPad Prism 5.0 software considering α = 5%. It was found that C. longa, curcumin, and aPDT using blue LED have an antifungal effect over C. albicans and C. tropicalis. The extract of C. longa 100 mg/mL and curcumin 200 μg/mL do not show toxicity on Galleria mellonella model.